2020
DOI: 10.1038/s41467-020-19472-8
|View full text |Cite
|
Sign up to set email alerts
|

Young adult-born neurons improve odor coding by mitral cells

Abstract: New neurons are continuously generated in the adult brain through a process called adult neurogenesis. This form of plasticity has been correlated with numerous behavioral and cognitive phenomena, but it remains unclear if and how adult-born neurons (abNs) contribute to mature neural circuits. We established a highly specific and efficient experimental system to target abNs for causal manipulations. Using this system with chemogenetics and imaging, we found that abNs effectively sharpen mitral cells (MCs) tuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 90 publications
(132 reference statements)
2
20
0
Order By: Relevance
“…Few brains with labeled neurons in contralateral OB or orbitofrontal cortex, which indicates that injections were not limited to the OB, were excluded from the analysis. As a side note, we observed mCherry expression in OB mitral cells and granule cells during development indicating expression of CaMKIIα in both cell types, similar to other studies (Liu, 2000;Shani-Narkiss et al, 2020), but in contrast to a study reporting that only granule cells in OB would express CaMKIIα (Zou et al, 2002).…”
Section: Retrograde Labeling Of Ob-projecting Neurons Across Developmentsupporting
confidence: 91%
“…Few brains with labeled neurons in contralateral OB or orbitofrontal cortex, which indicates that injections were not limited to the OB, were excluded from the analysis. As a side note, we observed mCherry expression in OB mitral cells and granule cells during development indicating expression of CaMKIIα in both cell types, similar to other studies (Liu, 2000;Shani-Narkiss et al, 2020), but in contrast to a study reporting that only granule cells in OB would express CaMKIIα (Zou et al, 2002).…”
Section: Retrograde Labeling Of Ob-projecting Neurons Across Developmentsupporting
confidence: 91%
“…One neural correlate of task difficulty could be the increased inhibitory responses by MCs (Figure 7), pointing to the role of inhibitory mechanisms as the basis for learning. [67][68][69] Dynamic changes in the OB following learning were previously reported. 17,18,23,68 Interestingly, when animals learned to discriminate between two very similar odor mixtures, the representation of odors by MCs diverged, improving discriminability.…”
Section: Functional Implications Of Category-related Plasticitymentioning
confidence: 66%
“…Some short axon cells that ramify their processes at the level of M/T cell lateral dendrites, on the other hand, are reported to contact granule cell dendrites (Eyre et al, 2008), thus may not be the direct source of perisomatic inhibition we observed. The EPL interneurons and granule cells both exhibit odour-locked responses (Miyamichi et al, 2013), and affect odour responses of M/T cells (Shani-Narkiss et al, 2020). Further, both types show state-dependent modulation (Kato et al, 2012;Kato et al, 2013).…”
Section: Discussionmentioning
confidence: 98%